LEARNING COMMUNICATION STRATEGY IN DIGITAL-BASED TRAINING INSTITUTIONS (CASE STUDY IN ONLINE TRAINING CLASS "SKILL ACADEMY") - Arina Muntazah; Rosiana Andhikasari; Rindana Intan Emeilia; Novalia Novalia (Jurnal Scientia, 2023)
This study aims to identify and explain the communication strategies used in online learning at digital-based training institutions. This study used a qualitative method with data collection techniques through interviews and observations in the Pre-Employment Skills Academy online training class. The study results show that the online learning communication strategy takes place effectively, namely by using the right technology in the form of e-learning platforms and mobile applications, there is an interaction between students and instructors, as well as clear and structured delivery of material.